The Pedagogy of Emancipation in Norge Espinosa’s Ícaros - Unruh, Vicky (Latin American Theatre Review, 2018)
This study argues that Norge Espinosa’s play Ícaros (2003) unpacks the longstanding, post-revolutionary Cuban connections among education, self-aware citizenship, and egalitarian ideals. In a contemporary version of the Icarus myth, Espinosa’s play stages the failed project of an older generation (embodied in three Dédalos) to create a new kind of super being through their offspring—the play’s six Ícaros, charged with achieving their creators’ unfulfilled ideals. Here the Dédalos-Ícaros myth, coupled with the modern superhero identities assigned to each Ícaro, enacts the pitfalls such projects activate and evokes comparisons with the revolutionary “new man” envisioned by Che Guevara, a version of such utopian ventures rooted in a Cuban audience’s cultural memory. Against the historical backdrop of a state pedagogy forged through the renowned 1961 post-revolutionary literacy campaign and institutionalized for decades throughout Cuba’s public education system, the teacher-student dynamic constituted an idealized workshop for creating such a “new man” and for empowering citizens through social change. In this context, Espinosa’s play de-mythifies the lingering ideal of the Revolution’s pedagogy as a path to social utopia, while at the same time reenergizing the concept of human education as an expansive intellectual adventure of the kind conceptualized by contemporary cultural theorist Jacques Rancière. Through the dynamic relationship between the six Ícaros and their protean teacher, Ariadna, the play juxtaposes the timeworn pedagogic practices that Ranciére would call “stultifying” with Ariadna’s simultaneous efforts to promote the Ícaros’ discovery of their own intellectual powers.